Estudo de correlações entre sondagens SPT e resultados de ensaios de penetração contínua PD e CPT para diferentes subsolos arenosos - Santos, Mirella Dalvi dos (2017)
Field tests used in geotechnical engineering are fundamental for knowledge of the underlying ground, estimate geomechnics parameters and, therefore, for foundations design. There are several types of tests: the Standard Penetration Test (SPT) is simple, cheap and have a large empirical experience; the Cone Penetration Test (CPT) is capable of tracing the resistance continuously; and the Dynamic Probing (DP) is simple and fast. Since there are limitations on their methodologies and equipments, equations that can describe the relationship between their results are recquired tools in geotechnical engineering, as they provide to the designer a tool capable to reduce costs and time, estimate soil parameters and afford a greater underground’s global knowledge. Therefore, this work aims to find correlations between SPT, CPT and DP tests for sands of Grande Vitoria, Espírito Santo. And more, evaluate the uncertainties involved in some previously published correlations in literature and to suggest adjustments, considering some soils’ properties. To do so, simple linear regression and residual’s analysis were carried out in four data sets from the region and other locations. It was found that the mean particle size, relative density and particle size distribution influence CPT-SPT and DP-SPT correlations. Geological origin and sleeve friction did not influence substantially in CPT-SPT correlations. Since the sandy soils’ heterogeneity implies in the need of correlations obtained at a regional level. Thus, this study does not aim to exhaust the subject about geotechnical tests correlations, but rather to recommend and stimulate the critical evaluation of previously published correlations and those that will be formulated in the future.